2010
DOI: 10.1152/jn.00983.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cross-Modal Plasticity in Early-Blind Subjects

Abstract: Lewis LB, Saenz M, Fine I. Mechanisms of cross-modal plasticity in early-blind subjects. J Neurophysiol 104: 2995-3008, 2010. First published July 28, 2010 doi:10.1152/jn.00983.2009. A variety of studies have demonstrated enhanced blood oxygenation level dependent responses to auditory and tactile stimuli within occipital cortex as a result of early blindness. However, little is known about the organizational principles that drive this cross-modal plasticity. We compared BOLD responses to a wide variety of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 95 publications
3
35
0
Order By: Relevance
“…However these responses have tended to be smaller than those found in the studies described above (Hagen et al 2002; Blake et al 2004; Beauchamp et al 2007; van Kemenade et al 2014). Our finding of a weak suppressive effect of tactile stimulation in the no task condition has also previously been observed (Ricciardi et al 2007; Lewis et al 2010). (Interestingly, a variety of studies show suppression of hMT+ when subjects attend to an auditory motion stimulus Lewis et al 2000; Strnad et al 2013; Jiang et al 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However these responses have tended to be smaller than those found in the studies described above (Hagen et al 2002; Blake et al 2004; Beauchamp et al 2007; van Kemenade et al 2014). Our finding of a weak suppressive effect of tactile stimulation in the no task condition has also previously been observed (Ricciardi et al 2007; Lewis et al 2010). (Interestingly, a variety of studies show suppression of hMT+ when subjects attend to an auditory motion stimulus Lewis et al 2000; Strnad et al 2013; Jiang et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…However a variety of studies have explicitly looked for, but failed to find, evidence of auditory motion responses in hMT+ (Lewis et al 2000; Saenz et al 2008; Bedny et al 2010; Lewis et al 2010; Alink et al 2012; Jiang et al 2014). Indeed, in an analysis closely analogous to that of Figure 5 it has been previously been shown by Saenz et al (Saenz et al 2008) that spurious auditory motion responses in hMT were elicited as a result of using group averaging methods to define hMT+.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the process of synaptic pruning, which typically removes about 40% of the synaptic connections of visual cortex in early life (41), is limited in the case of early sensory deprivation. A decreased level of pruning might, at least in part, underlie the auditory-to-visual cross-modal plasticity in the early blind (42)(43)(44)(45): the absence of visual input during early development allows the synaptic connections to strengthen in blind individuals (46). This cross-modal plasticity predicts a stronger response in visual cortex of blind persons when auditory stimuli are processed and perhaps could explain why we observed a stronger selectivity for auditory stimuli in VTC of the congenitally blind participants.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have reported that the occipital cortex of CB responds quite indifferently to a variety of cognitive tasks, suggesting that some common factors (i.e., attentional) rather than specific cognitive processes may contribute to the unselective occipital activity observed in this population (5)(6)(7)(8). In contrast, other studies do suggest that distinct regions of the visually deprived occipital cortex may show functional specialization that is to some extent comparable to what is known in SI (9).…”
mentioning
confidence: 89%